Improving the Quality of Vocational High School Graduates Through Partnership Models with Industry - Muhammad Yusuf; Abubakar Abubakar; Siraj Siraj; Safwan Safwan; M. Firdaus (LPPM Universitas Malikussaleh, 2024)
The quality of Vocational High School graduates is considered insufficient and does not meet the requirements for performing high-skill jobs, leading to the highest open unemployment rate compared to other education levels. A preliminary study conducted in several Vocational High Schools with machining competency fields in Lhokseumawe found a systematic empirical phenomenon. Graduates are unable to meet the industry's needs, resulting in difficulties in entering the workforce in line with current conditions. This research specifically aims to find a partnership model for vocational high schools with machining competencies in facing the 4.0 disruption era. The importance of this research is to develop a partnership model between Vocational High Schools and industry in both quality and quantity, requiring optimal management. Therefore, continuous studies are needed to maximize management in partnership relations so that the quality of vocational education continues to improve. This research uses a qualitative approach with a case study method. Data analysis follows the Miles & Huberman model, which consists of data collection, data presentation, data reduction, and conclusion. The research results show that an effective partnership model should include continuous collaboration between educational institutions and industry, appropriate training programs, and internship opportunities to provide practical experience. Routine evaluation and adjustment of this model will ensure that the partnership remains relevant and beneficial amid the rapid changes in the 4.0 disruption era